(untitled) (Medical Forum Monthly, 2024)
Objective: To analyze the complications associated with use of reverse sural artery flap to provide soft tissue coverage for lower third of leg and heel defects. Study Design: Retrospective study Place and Duration of Study: This study was conducted at the Plastic Surgery Department at Liaquat National Hospital from February 2014 to December, 2016 Materials and Methods: Patient demographics, physical and clinical examination retrieved. Doppler ultra sonography was used to identify perforating vessels to aid in the planning of a pivot point. The skin island was outlined to match the recipient site defect than the flap was dissected and inset done. Patients were followed for 1 month and outcomes were recorded. Results: There were 136 patients were included with lower third of leg and heel wound and exposed structures like tendons, bone, nerve and vessels. Out of 136 cases 44 (32.4%) cases had complications. Complete flap necrosis was occurred in 19.1% cases, infection occurred in 11% and partial flap necrosis occurred in 8.1% cases. Conclusion: The distally based reverse sural artery flap is a better option for coverage of soft tissue defects in the distal 3rd of the leg and proximal foot.